Implementasi Sistem Pengolahan Sampah Sirkular Berbasis Aplikasi untuk Mengoptimalkan Potensi Limbah Organik Desa Benteng Gajah - Indira Djiloi; Nur Hikmawati Alwi; Muhammad Alif Maulana; Muhammad Yogi Naupal; Muhammad Ilham Nur Furqan; Putri Yasmin Nur Shabrina; Masyita BJ; Rafiqa Awalina Putri; Haikal Akbar; Sahriyanti Saad (Institut Pertanian Bogor, 2026)
Benteng Gajah Village, Tompobulu District, Maros Regency, South Sulawesi, lacks a household waste management system. The majority of residents work as farmers, livestock breeders, and furniture craftsmen, resulting in high organic waste production. This situation exacerbates issues at the final processing site (TPA), as organic waste is the largest emitter of methane gas during landfill processes. Methane has a global warming potential (GWP) up to 34 times greater than CO2. This community service program aimed to establish Rumah Olah as a circular economy-based organic waste processing center integrated with the Olah.ind application to enhance the economic value of organic waste. The program employed participatory rural appraisal (PRA) and andragogical approaches through observation, interviews, focus group discussions (FGD), demonstration and hands-on practice. The program includes preparatory phases, application development, and empowerment through organic waste processing via maggot farming, organic fertilizer production, aquaponics, and the use of the Olah.ind application. The results showed that Rumah Olah was successfully as a community-based organic waste processing center integrated with the Olah.ind application. The system enables residents to sort and deposit organic waste, which is subsequently processed into value-added products, including maggot, compost, aquaponic vegetables, and fish. Pre-test and post-test evaluations demonstrated that participants’ knowledge of organic waste management and the use of the Olah.ind application increased from an average score of 28% in pre-test to 92% in post-test. Overall, the Rumah Olah has fostered an inclusive and sustainable community empowerment ecosystem for circular organic waste management and the production of economically valuable products.